ANALISIS PENGARUH PARIWISATA, KETERBUKAAN PERDAGANGAN DAN PENDIDIKAN TERHADAP TINGKAT KEMISKINAN DI ASEAN-5 - Elverda, Shine (UPT Penerbitan Universitas Jember, 2025)
This study aims to analyze the influence of tourist arrivals, tourism receipts, trade openness, and education on poverty levels in the ASEAN-5 between 2000 and 2023. Poverty levels in the ASEAN-5 countries (Indonesia, Malaysia, the Philippines, Thailand, and Vietnam) remain a significant challenge despite the region's significant economic potential, particularly in the tourism and trade sectors. The analysis was conducted using secondary data from the World Bank and United Nations Development Programme and processed using E-Views 12. The results indicate that tourist arrivals have a positive and significant effect on poverty, while tourism receipts and trade openness have a negative and significant effect. These findings emphasize the importance of equitable distribution of economic benefits for these sectors to truly impact poverty alleviation. Furthermore, mean years of schooling were also found to have a negative and not significant effect on poverty, underscoring the role of education in improving the quality of human resources. This study provides policy recommendations to maximize the potential of tourism and trade in an inclusive and sustainable manner to reduce poverty in the ASEAN-5 region.